DepED's decentralization policy among NCR schools a model - Abelardo, Lannie A. (2007)
This study aimed to look into the school administrators' implementation and teachers' perception of the implementation for decentralization in the educational system in public elementary schools. The study was conducted through the survey method at a sample of 18 schools in four divisions in NCR. Interviews were done from the nearest and farthest schools in each division. Results showed that in service trainings in school are regularly conducted as part of the administrative role. The school head, principal, and administrators need to have a full orientation regarding the system of decentralization. A new breed of principals is required to achieve the goals of decentralized school management. Teachers should be encouraged to develop good professional relationship to superiors to establish a favorable atmosphere for decentralization.
"October 2007."
Thesis (M.A. Educational Administration)--University of the Philippines, Diliman.
Keywords: School management and organization -- Philippines -- National Capital Region; Education and state -- Philippines -- National Capital Region; School autonomy -- Philippines -- National Capital Region; Schools -- Decentralization -- Philippines -- National Capital Region